CARDIOVASCULAR RISK AND OUTCOME IN PATIENTS WITH HYPERTENSIVE EMERGENCIES AND URGENCIES IN AN EMERGENCY DEPARTMENT. AN ITALIAN GREEK COLLABORATION. (April 2021) - Muiesan, ML; Salvetti, M; Fragoulis, C; Paini, A; Aggiusti, C; Bertacchini, F; Stassaldi, D; Tarozzi, L; Dimitriadis, K; Konstantinidis, D; Kasiakogias, A; Kalos, T; et al.
Abstract : Objective: Background: at present, few data are available on the prognosis of hypertensive emergencies and urgencies admitted to Emergency Departments (ED). The aim of our study was to evaluate the incidence of total and cardiovascular events during follow-up in hypertensive patients admitted in 2 ED in Italy and Greece with hypertensive emergencies or urgencies. Design and method: Methods: medical records of patients aged > 18 yrs, admitted to the ED with blood pressure values > = 180 mmHg (SBP) and/or > = 120 mmHg (DBP) were collected and analysed (24% of patients were classified as "hypertensive emergency" and 76 % as "hypertensive urgency"). Data in 1218 patients (556 men and 662 women, mean age 70 + 13 years) were analysed; the mean duration of follow-up after admission to the ED was 19.5 + 7 months years. Results: Results: During the follow-up cardiovascular events occurred in 148 patients (69 cardiac events, 43 cerebrovascular events). In 272 pts (22 %) a new episode of acute BP rise was recorded. A total of 87 deaths was recorded during follow-up (in 28 patients for cardiovascular causes). All cause and CV mortality were greater in patients with a previous hypertensive emergency (14.7 vs 4.7 %, chisquare p = 0.0001 and 5.8 vs 1.2% chisquare p < 0.0001 for all-cause and for CV mortality, respectively). The incidence of non fatal cardiovascular events was 10, 11 and 2, 11 per 100 patient-years in patients with hypertensive emergency and urgency, respectively and similar results were obtained when we considered separately the occurrence of cerebrovascular events. Conclusions: Conclusions: admission to the ED for hypertensive emergencies identifies hypertensive patients at increased risk for fatal and non fatal cardiovascular events. Our results underline the need for an accurate follow-up in patients with hypertensive emergencies and urgencies.